The Antics of Semantics in International Law - McAdam, Marika (Anti-Trafficking Review, 2018)
Response to the ATR Debate Proposition: ‘It is important and necessary to make clear distinctions between (irregular) migrants, refugees and trafficked persons.’ Whether a person is given a loaded label like ‘irregular’ migrant, refugee or trafficked person, can make the difference between arrest and protection, or between deportation and asylum, or between return to an uncertain fate and assistance for a decent life. In short, the distinctions we make in the language of international law may mean the difference between life and death.